Anomalous Hammett S Plot in the Quenching of Ru(Bpy)3 2+ Phosphorescence by P-Substituted Phenols - Lissi-Gervaso, E; Calderon-Espinoza, C; Calderon-Espinoza, C; Ahumada-Escandon, M; Ahumada-Escandon, M (Elsevier B.V., 2016)
Tris(2,2′-bipyridine) Ru(II) (Ru(bpy)32+) phosphorescence is readily quenched by p-substituted phenols in a bimolecular process whose rate, in aqueous solution, is determined by the pH of the solution and the electron-affinity of the substituent. A Hammett s type plot based on data obtained at pH 10.4 in terms of σ parameters conforms to a parabola with a minimum rate for phenol and two branches, one comprising compounds with negative σ values (electron donors) and other with positive σ values (electron acceptors groups). This anomalous behaviour takes place at a constant pH and it can be explained in terms of two quenching mechanisms: a simple electron transfer from the phenolate to the Ru(II) complex when pKa ≪ pH, and a PCET (proton coupled electron transfer) mechanism for compounds where the protonated phenol predominates (pKa > pH). © 2016 Elsevier B.V. All rights reserved.